RECONSTRUCTIVE PLASTIC SURGERIES IN PATIENTS WITH MALIGNANCIES OF TONGUE AND FLOOR OF THE MOUTH. TYPES OF PLASTICS - Z. A. Radjabova; D. A. Rakitina; A. V. Gurin; N. I. Korkola; R. A. Nazhmudinov; I. V. Dunaevsky (Опухоли головы и шеи, 2015)
Issues of tissue defects replacement after radical surgery for tumors of the head and neck do not lose their relevance. The article presents the results of plastics and replacement of the perforating combined defects of the floor of the mouth, portion of the upper and lower lips, the angle of the mouth, cheeks, neck lateral parts with simultaneous reduction of the configuration and function of the operated organs. Depending on the depth and nature of the existing tissue defect various methods of plastics were applied using arterialized flaps on the vascular pedicle in a free and non-free version. Satisfactory cosmetic and functional results were achieved in patients allowing to improve life quality and to adapt socially.